AN ANALYSIS OF MATHEMATICAL’S WRITING OF STUDENT’S ABILITY ON THE CLASS VIII - Syarifah, Dita Latifatu; Taufik, Marhan; Cholily, Yus Mochamad (MEJ (Mathematics Education Journal), 2017)
The research has a goal to describe writing mathematical student capabilitybased on mathematics expression aspect and writing text aspect on thesystem equation linear two variable lesson.The research is using qualitativeapproach which creature of descriptive. The collecting technique of datawhich done is about the result of answering test. The result’s analysis ofthe research student capability on writing mathematical expression andwriting text which be on the system equation linear two variable matter isabout the student can writing mathematics model which suitable with thematter has given, but did not write the formula completely. The result’sanalysis of test on the writing text aspect, student can write the symbolexactly but there is notconsistently and less coherent on writing steps. Ashortage of mathematics expression and writing text because of student lesson understanding what it asked on the matter. The abilities’ result of studentsmathematics written based on expression mathematics on the highcathegories and get average about 67,54%, while getting result of writingtext on the middle cathegories as about 60,52%.